Effect of Tear Location on Propagation of Isolated Supraspinatus Tendon Tears During Increasing Levels of Cyclic Loading. (18th February 2015) - Araki, Daisuke; Miller, R. Matthew; Fujimaki, Yoshimasa; Hoshino, Yuichi; Musahl, Volker; Debski, Richard E.
Abstract : Background: The morphology of the supraspinatus tendon may affect tear propagation. It was hypothesized that tears located in the anterior third of the supraspinatus tendon would propagate more readily and would require lower loads to reach critical amounts of tear propagation than those located in the middle third of the supraspinatus tendon. Methods: Twenty-three fresh-frozen human cadaveric shoulders were tested under increasing levels of cyclic loading. Tears were created in the anterior third (Group A, n = 10) or the middle third (Group M, n = 13) of the supraspinatus tendon. The maximum load at which a critical tear retraction was reached and the tear area for the final loading set were compared between groups. A correlation analysis was also performed for age compared with maximum load. Results: No significant differences were found between the anterior-third tear group (Group A) and the middle-third tear group (Group M) in maximum load (p = 0.09) or tear area (p = 0.6). However, Group A first reached a 100% increase in tear size at a significantly lower load than Group M (p = 0.03). Strong negative correlations were detected between age and maximum load in Group A (τ = −0.82) and Group M (r = −0.63). Conclusions: Other factors being equal, tears in the anterior supraspinatus tendon may propagate more readily than tears in the tendon's middle part. Age may be a factor for tear propagation. Clinical Relevance: Older patients and patients with tears in the anterior supraspinatus should be followed especially carefully.